Implementation Philosophy and Principles Science of Education in Learning at SMAN 1 Kota Padang - Anggraini, Silvia; Fitrisia, Azmi; Erianjoni, Erianjoni (Master Program of Social Science Education of Universitas Negeri Padang, Indonesia, 2025)
Education is a fundamental pillar of a nation’s development, serving as a critical instrument in producing a high-quality generation capable of addressing increasingly complex and dynamic global challenges. To achieve this vision, the implementation of various educational foundations—philosophical, psychological, sociological, and cultural—is essential in shaping a comprehensive and effective learning environment. This article aims to analyze how different educational foundations are implemented in the educational practices at State Senior High School 1 (SMAN 1) Padang City, West Sumatra, Indonesia. The study adopts a qualitative research approach, employing data collection techniques such as in-depth interviews with teachers, classroom observations, and analysis of school documents related to learning strategies and policies. The research findings indicate that SMAN 1 Padang has made various efforts to incorporate educational foundations into the teaching and learning process. These include applying learner-centered approaches, integrating local cultural values, and fostering student potential in accordance with psychological development stages. However, the study also reveals several challenges that hinder optimal implementation, such as limited teacher training on educational theories, inconsistent application across subjects, and insufficient institutional support for long-term integration. These findings suggest that to effectively realize national education goals, there needs to be a stronger synergy between educational theories and practical implementation in schools. Continuous professional development for teachers, improved collaboration among stakeholders, and school policies that support the application of educational foundations can play a pivotal role in bridging the gap between theory and practice.